Exploring the industrial importance of a miracle herb Withania somnifera (L.) Dunal: Authentication through chemical profiling, in vitro studies and computational analyses. (October 2022) - Tousif, Muhammad Imran; Nazir, Mamona; Saleem, Muhammad; Tauseef, Saba; Uddin, Reaz; Altaf, Muhammad; Zengin, Gokhan; Ak, Gunes; Ozturk, Refiye Beyza; Mahomoodally, Mohamad Fawzi
Abstract: Withania somnifera (L.) Dunal has been identified as a miracle herb, thus the present study was carried out to investigate W. somnifera growing in Cholistan Desert for its secondary metabolic profile and various biological activities. The WS-C fraction of methanolic extract (WS-M) of W. somnifera was found rich in phenolics (39.96 ± 0.90 mg GAE/g extract), and it exhibited significant DPPH (30.69 ± 0.78 mg TE/g extract) and ABTS (113.60 ± 2.41 mg TE/g extract) free radical inhibitory activities, cupric (Cu +2 ) and ferric (Fe +3 ) reducing potential as 157.51 ± 2.10 and 124.60 ± 0.34 mg TE/g extract. The same fraction also exhibited strong total antioxidant capacity (1.39 ± 0.01 mmol TE/g extract) in phosphomolybdenum assay. Other fractions displayed relatively lower potential. In metal-chelating assay, WS-M, WS-E and WS-B showed nearly equal potential with values of 22.35 ± 0.62, 20.96 ± 0.12 and 22.10 ± 0.75 mg EDTAE/g of the extract, while in AChE, BChE and tyrosinase inhibitory assay, again WS-C fraction was most active (7.50 ± 0.21, 8.01 ± 0.53 mg GALAE/g extract and 36.81 ± 0.20 mg KAE/g extract, respectively). In α-amylase and α-glucosidase inhibitory assay, WS-C showed significant potential with values as 0.74 ± 0.01 and 1.14 ± 0.004 mmol ACAE/g extract, respectively. UHPLC-MS analysis of WS-C fraction leads to identify 100 secondary metabolites of phenolic, withanolide, terpenoid, steroid, lignin, flavonoid and limonoid classes of compounds. This profile makes W. somnifera a fascinating plant. These findings were validated by computational studies, which revealed that selected compounds exhibited high binding free energy and inhibition constants with the enzymes tested. Pearson correlation analysis clearly established that the phenols in the tested extracts were the main players as antioxidants and enzyme inhibitors, which was also substantiated through Principal Component Analysis (PCA). These results suggest that chloroform might be suitable for preparing further applications with W. somnifera extracts, and this plant can be placed in the list of top-selling herbs, and may become source of commercial assets. Graphical Abstract: ga1 Highlights: This study unveils metabolic profile and biological activities of Withania somnifera . The Chloroform (WS-C) fraction showed high phenolic contents and bioactivities. UHPLC-MS analysis of WS-C fraction leads to identify 100 secondary metabolites. Docking studies validated the enzyme inhibition activities of the extract. Multivariate statistical analysis established relationship between phenolics and bioactivities.